Historiography of Relations Between the States of Amir Temur and Azerbaijan - Rakhmatullaeva, Ozoda Rustamovna; Shukurov, Nuritdin Rakhimovich (European Journal of Life Safety and Stability (2660-9630), 2022)
In the second half of the 14th century, trade relations in the lands of Azerbaijan almost stopped. One of the reasons for this is that the semi-nomadic Turkmen tribes of the Black Sheep settled and fortified the strong fortresses of Alanchuk, Aydin and Avnik in Eastern Anatolia, where they plundered the caravans that passed through these lands. Especially, Azerbaijan suffered a lot from Kara Yusuf, the emir of the Black Sheep, and Sultan Ahmad Jaloyir, the governor of Iraq. In addition, in 1386-1387, another great enemy of the Golden Horde, Tokhtamysh, who threatened Azerbaijan, returned to the country several times This article discusses the history of the military campaign of Amir Temur in Azerbaijan, the main goal of the campaign, the elimination of predatory and robber raids by Amir Temur, the approach of researchers to this issue.